Community Structure epi-macrozoobentos in water of Pandan Island Aquatic Tourism Area Pieh Island West Sumatera - Sihaloho, Indra Y P; Samiaji, Joko; Nasution, Syafruddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Epi-macrozoobentos are animals that live on the surface of a water base substrate and are larger than 1 mm in size. This study aims to determine the structure of epi-macrozoobenthic community which includes: species composition, abundance, diversity, uniformity, dominance and the relationship between the total organic content of sediment to epi-macrozoobenthic abundance. Environmental parameters measured include physics-chemical parameters of waters (temperature, velocity, salinity, pH and DO) as life-supporting factors of epi-macrozoobentos. The species of epi-macrozoobentos in the waters of Pandan Island were found to be 17 species from 14 families, 7 classes and 14 genera with species composition ie 74% Gastropoda class, Echinoidea 9.6%, Malacostraca 8.6%, Bivalva 3%, Asteroidea 2.6 % and Holothuridea 2.2%. Epi-macrozoobenthic abundance in Pandan Island waters ranged from 4.5 to 6.6 ind / m2 with an average of 5.3 ind / m2. The diversity index values ranged from 2.45 to 2.86, the dominance index ranged from 1.14 to 1.21 and the uniformity index ranged from 0.62 to 0.81. The total organic content of sediments ranged from 1.70 to 2.57%. Based on the diversity index (H ') of Pandan Island waters classified as moderate and medium diversity. In general, the state of the chemical physics of Pandan Island waters can still support the life of epi-macrozoobenthic organisms.Keywords: Community structure, epi-macrozoobentos, Organic matter, Pandan Island.